The price of power : how Mitch McConnell mastered the Senate, changed America, and lost his party - Tackett, Michael (Simon & Schuster, 2024)
The first definitive biography of Mitch McConnell, revealing the personal and political life of one of the most powerful senators in American history. Drawing on thousands of pages of archival materials, letters, and more than 100 interviews with associates, colleagues, and McConnell himself, Michael Tackett pieces together the story of McConnell's early life, his formative battle with polio as a young child, and the teenage infatuation with politics that persisted through his four decades in the Senate.